Pengembangan Kurikulum Dan Pendekatan Pembelajaran Pendidikan Agama Islam Kontekstual - Sukino Sukino (Belajea: Jurnal Pendidikan Islam, 2023)
The Learning Curriculum needs to keep up with the times so the academic texts in it need to be updated. The research explains the concept of curriculum development and Islamic education learning with a contextual approach. This study uses the type of library research (Library Research). This research was conducted by conducting an in-depth analysis of various sources relevant to the issues to be discussed. Data collection was carried out by collecting reference books, scientific journals, and e-book online media information. The results of the study stated that several things such as the curriculum and the development of Islamic education learning must be returned to their philosophical roots with consideration of supporting and inhibiting factors for success. Factors that must be considered are curriculum content, curriculum implementation models, and curriculum evaluation tailored to the needs of students, the world of work, and society. To realize this, PAI teachers must be able to apply a contextual approach by following the principles of constructivist learning, implementing active learning strategies, and using sophisticated technological media and facilities.